Playing the race game: a performance-as-research project investigating our complicity in performing race - Neill, Hamish Mabala Mapoma (My University, 2015)
This research report consists of a performance-as-research project, titled T for Tea, accompanied by a written report. This document serves as fulfilment of the written requirement. The document is written within a Performance-as-Research paradigm, and includes a performance style of writing that reaffirms the intention, ethos and creative performativity established from the onset of the research project. Hence, the document presents an enhanced dialogue about the complexities of race as a social phenomenon, with specific reference to South Africa. The study sought to unravel the inherent complicity that reinforces the on-going notions of ‘race’, ‘racialisation’ and the performance thereof, as essentialist truths. The written document is constructed as a dialogue using the researcher/performer as the vehicle to grapple with the study’s intention of using an auto-ethnographic performance methodology as a critical tool of enquiry into the phenomenon of race in the South African context. This performative writing style is a characteristic of this methodology and is used to express argument while constructively disrupting norms, with the intention of inspiring analysis, reflection and new expression in academia of social phenomena. The reader is introduced to the dilemma of ‘race’ through this dialogue between researcher/ performer as an ‘essentialist performance’ in the prologue. This leads to an interrogation of why the study focuses on the choice of ‘complicity’ as a key to understanding the social performance of race within the South African context. The study then turns its attention to the notion of research and researches the evolution of the researcher from ethnographer to autoethnographer. This sets the stage for an interrogation of the making of the play T for Tea. Here the role of the performer as ethnographer is explored. The writer attempts to demonstrate the move from a representational form of performance to a performance landscape of construction, agency and interpretation. The study concludes, through the performed dialogue, that there is a critical need to find ways to unearth complicit practices of ‘race’ and ‘racialisation’. Performance that embodies race can be both essentialist and complicit in the on-going culture of racism in South Africa. An autoethnographic approach, within a larger Performance Studies paradigm to performance, allows the researcher/performer an opportunity to examine, expose and perform race in ways that can help liberate and move away from a historical paradigm that undermines our greater humanity.
MA (Dramatic Arts) Research Report